2012
DOI: 10.1152/ajplung.00325.2010
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal imatinib treatment reduces pulmonary vascular remodeling in a rat model of congenital diaphragmatic hernia

Abstract: The pathophysiology of congenital diaphragmatic hernia (CDH) is constituted by pulmonary hypoplasia and pulmonary hypertension (PH). We previously reported successful treatment with imatinib of a patient with CDH. This study examines the effect of antenatal imatinib administration on the pulmonary vasculature in a rat model of CDH. Pregnant rats were given nitrofen to induce CDH. Controls were given olive oil. Half of the CDH fetuses and half of the controls were treated with imatinib antenatally E17-E21, rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…Neointimal formation after vessel injury is a complex process involving the proliferation and migration of VSMCs [21]. Apoptosis is also important in this process [34,35]. In this study, PD168077 significantly reduced the balloon injury caused neointimal hyperplasia in rat carotid artery.…”
Section: Discussionmentioning
confidence: 65%
“…Neointimal formation after vessel injury is a complex process involving the proliferation and migration of VSMCs [21]. Apoptosis is also important in this process [34,35]. In this study, PD168077 significantly reduced the balloon injury caused neointimal hyperplasia in rat carotid artery.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, anti-VEGF therapy could increase the expression of PDGFs, suggesting the activation of PDGFs/PDGFRs as a compensatory pathway in the absence of VEGF and the PDGFs/PDGFRs axis as a promising target for the treatment of angiogenic diseases [15,26,27]. Imatinib was reported to inhibit the expression and activation of PDGFRs in vitro and in vivo by targeting the ATP-binding site of tyrosine kinases of PDGFRs and inhibiting their biological effect [28,29]. In the present study, we found that imatinib could effectively ameliorate retinal angiogenesis by suppressing the expression and phosphorylation of PDGFRs in the OIR model, suggesting that imatinib may be a novel anti-angiogenesis drug used either alone or in combination with anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the herbicide nitrofen (2,4-dichloro-p-nitrophenyl ether) to pregnant rats on day 9 (D9) of gestation induces PH and diaphragmatic defects in the offspring with striking similarities of the pathologies observed in human CDH (Beurskens et al, 2007;Corbett et al, 2012;Luong et al, 2011). It has been recently reported that the BMPR2 target proteins PDGF-BB and MCP-1 are significantly increased in nitrofeninduced CDH lungs (Chang et al, 2012;Gosemann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%